50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-3728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fuel Injection and Mixing Characteristics on Pulse-Combustor Performance at High-Pressure

Abstract: Recent calculations of pulse-combustors operating at high-pressure conditions produced pressure gains significantly lower than those observed experimentally and computationally at atmospheric conditions. The factors limiting the pressure-gain at high-pressure conditions are identified, and the effects of fuel injection and air mixing characteristics on performance are investigated. New pulse-combustor configurations were developed, and the results show that by suitable changes to the combustor geometry, fuel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…The results obtained in Ref. 5 further revealed that two counter-rotating vortices were formed in the pulsecombustor, and that the fuel was being split between these two vortices. The combustion occurring in the secondary vortex, located further away from the combustor head-end, was not being confined as efficiently as the combustion occurring in the primary vortex, potentially affecting negatively the pressure gain in the combustor.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The results obtained in Ref. 5 further revealed that two counter-rotating vortices were formed in the pulsecombustor, and that the fuel was being split between these two vortices. The combustion occurring in the secondary vortex, located further away from the combustor head-end, was not being confined as efficiently as the combustion occurring in the primary vortex, potentially affecting negatively the pressure gain in the combustor.…”
Section: Introductionmentioning
confidence: 88%
“…Preliminary calculations of pulse-combustors-ejector configurations operating at high-pressure conditions (10 bar) produced pressure gains significantly lower than those observed experimentally and computationally at atmospheric conditions 4 . A recent study 5 identified the factors limiting the pressure-gain at highpressure conditions and investigated the effects of fuel injection and air mixing characteristics on performance. New pulse-combustor configurations were developed in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsejet combustors are prone to being highly sensitive to the mixing inside; in some scenarios, significantly more so than traditional combustors. Yungster et al 34 have shown that depending on the nature of coupling between the vortex formation after the valves and the combusting region (combustion occurring on the inner Pekkan and Nalim (2003). 22 region of the vortex vs. that occurring outside the vortex, near the wall, which can produce hotspots) there could be a factor of two increase in the observed NOx emissions index.…”
Section: Pulsejetmentioning
confidence: 99%
“…Hence, a novel method was used to sample a PDC, wherein a type of pseudo-averaging of emissions is performed by aggregating the produced gases from four consecutive tests into a container, and then sampling the stored gases in it. 45 Tests were run for about 2.5 s, whereas sampling started 34 and ended a seventh of a second after ignition and before shutoff, respectively. A wall-mounted probe at the end of the PDC tube was fitted with the sampling probe.…”
Section: Pulse Detonation Combustorsmentioning
confidence: 99%